Hydrogen‐Bonds‐Mediated Nanomedicine: Design, Synthesis, and Applications. Issue 18 (20th September 2022) - Chen, Senbin; Wu, Yanggui; Lortie, Frédéric; Bernard, Julien; Binder, Wolfgang H.; Zhu, Jintao
Abstract : Front Cover : Article 2200168 by Senbin Chen, Jintao Zhu, and co‐workers summarizes the design and synthetic routes towards Hydrogenbonded nanomedicines, focuses on the growing understanding of the structure‐function relationship for efficient cancer treatment. A guidance for designing new Hydrogen‐bonded intelligent theranostic agents is proposed, to inspire more successful explorations of cancer nanotheranostics and finally to promote potential clinical translations.